Inteligência artificial no Poder Judiciário: ética e eficiência em debate - Ribeiro, Márcio Vinicius Machado (2021)
Artificial intelligence (AI) has become part of our daily lives, being used in various sectors. Machines that are used for AI are capable of interacting with humans and the environment. However, most of us have little or no understanding and knowledge about how these intelligent systems work and generate results and actions that can impact our lives. The objective of this work is to show the efforts that have been made so that the legal systems that use AI can serve their users in a more agile, efficient and ethical way, reducing the time of court proceedings. Many algorithms used for machine learning cannot be analyzed or interpreted by humans, being somewhat obscure in the eyes of users. Thus, we can say that the acceptance and insertion of this technology in our lives can generate many questions because we do not understand how it works and is developed. However, we can say that artificial intelligence is a new area, despite having been around for many years, but only now that it has taken on great proportions. The objective of this research is to work on issues related to clarification, on the issue of intelligent agent reasoning, so that the final result is more reliable, efficient and ethical. We can point out that systems in this way can be audited to prevent problems and misconceptions of use, and to hold those involved in development accountable as a result of the result. In this way, passing through the understanding and acceptance of those who developed it and the customers. We show the new mechanics used in our legal environment, through the insertion of Artificial Intelligence and new technologies in the Judiciary. Bringing information about how Artificial Intelligence emerged and how information is generated to build a system closer to human reality. The challenges are great for the AI system, with new technologies and concerns when we take the legal hold to review, evaluate and give a conclusion to judgment. This work mentions about the impact of AI (Artificial Intelligence) in society and in the legal environment, I talk about the concept of Machine Learning and Deep Learning. As a result of the IA Implementation, in terms of agility in the automation of processes, and what are the benefits. With the Coronavirus pandemic, the Judiciary was imbued with the need to use technology so that its activities would not be stopped due to the imperative need for social distance. Thus, new themes emerged from this practice, i.e., ethics as a guide for legal actions, speed as a key to access to justice and efficiency as a catalyst for the use of technologies. We use Data Quantitative Research Method. We also intend to draw a parallel between legal consequentialism and automation in this environment in which Artificial Intelligence is the center of the development of Law. Our observations generated a set of guidelines for the development of the AI system